FDVis: the Interactive Visualization and Steering Environment for the Computational Processes Using the Finite-Difference Method - Kurtinaitis, A.; Vaicekauskas, R.; Ivanauskas, F. (Nonlinear Analysis: Modelling and Control, 2003)
In this paper a specialized software environment for visualization and steering of finite-difference computations is presented. The user requirements are identified and the architecture of the environment is summarized. The advantages of such a specialized system over some available universal visualization systems are discussed and conclusions and future research issues are given.
Keywords: scientific visualization; computational steering; finite-difference; numerical simulation